Di-mu-thiocyanato-kappa N-2:S;kappa S-2:N-bis({2-morpholino-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}(thiocyanato-kappa N)cadmium) - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H.; Hisham, N.A.I. (International Union of Crystallography, 2011)
In the title complex, [Cd-2(NCS)(4)(C13H19N3O)(2)], the two Cd-II ions are bridged by a pair of thiocyanate N:S-bridging ligands around an inversion center. One terminal thiocyanate N atom and one N,N',N ''-tridentate Schiff base ligand complete a distorted CdN5S octahedral geometry about each Cd-II atom. In the crystal, the Schiff base aromatic rings of adjacent molecules are arranged above each other into infinite chains along the a axis with alternate centroid-centroid separations of 3.5299 (13) and 3.7857 (13) angstrom.